Grasping the changing world : anthropological concepts in the postmodern era - Hubinger, Václav (European Association of Social Anthropologists., 1996)
"Grasping the Changing World collects papers read at the second biennial EASA conference in Prague in 1992. The conference took place in an extraordinary 'postmodern' setting. With the fall of the communist regimes in Central and Eastern Europe old certainties and time-honoured concepts had become obsolete; at the same time, anthropology too was in upheaval, and long-established patterns of thought seemed inadequate to grasp the rapidly changing realities. These doubts and tensions are reflected in this collection." "The first half of Grasping the Changing World focuses on ways of conceptualising, modelling and perceiving the present, while the second half reassesses the theoretical strength or otherwise of social anthropology as a modern social science. Combining methodological rigour and originality, this collection will make invaluable reading for all students of social anthropology, sociology and politics."--Jacket